The role of probiotic therapy on clinical parameters and human immune response in peri-implant diseases: a systematic review and meta-analysis of randomized clinical studies - López-Valverde, Nansi; López-Valverde, Antonio; Blanco Rueda, José Antonio (Frontiers in Immunology, 2024)
Background-Peri-implant diseases (peri-implant mucositis and peri-implantitis) are pathologies of an infectious-inflammatory nature of the mucosa around dental implants. Probiotics are microorganisms that regulate host immunomodulation and have shown positive results in the treatment of peri-implant diseases. The objective of the systematic review and meta-analysis was to evaluate the efficacy of probiotics in the treatment of peri-implant oral diseases. Methods-According to the PRISMA guidelines, the research question was established: Are probiotics able to favorably modify clinical and immunological biomarkers determinants of peri-implant pathologies? and an electronic search of the databases MEDLINE/PubMed, Embase, Cochrane Central, Web of Science, (until December 2023) was performed. Inclusion criteria were established for intervention studies (RCTs), according to the PICOs strategy in subjects with peri-implant pathology (participants), treated with probiotics (intervention) compared to patients with conventional treatment or placebo (control) and evaluating the response to treatment (outcomes). Results-1723 studies were obtained and 10 were selected. Risk of bias was assessed using the Cochrane Risk of Bias Tool and methodological quality using the Joanna Briggs Institute for RCTs. Two meta-analyses were performed, one to evaluate probiotics in mucositis and one for peri-implantitis. All subgroups were homogeneous (I 2 =0%), except in the analysis of IL-6 in mucositis (I 2 =65%). The overall effect was favorable to the experimental group in both pathologies. The analysis of the studies grouped in peri-implantitis showed a tendency to significance (p=0.09). Conclusions-The use of probiotics, as basic or complementary treatment of periimplant diseases, showed a statistically significant trend, but well-designed studies are warranted to validate the efficacy of these products in peri-implant pathologies.